PENGARUH LATIHAN RESISTANCE BAND DAN PLYOMETRIC TERHADAP KECEPATAN TENDANGAN SABIT PADA ATLET PENCAK SILAT PERGURUAN PAT BAN BU KOTA PADANG - Ikhsan Ilham; Desi Purnama Sari; Jeki Haryanto; Juanda Putra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the suboptimal speed of sickle kicks among athletes of Pat Ban Bu Pencak Silat Academy, Padang City, which affects scoring opportunities during matches. Sickle kick speed is an important component in pencak silat performance and is influenced by lower limb power, neuromuscular coordination, and training methods. This study aimed to determine the effect of resistance band and plyometric training on sickle kick speed among Pat Ban Bu athletes. The research employed a quasi-experimental method using a One Group Pretest-Posttest Design. The population consisted of 68 athletes, while 20 athletes were selected through purposive sampling. The instrument used was a 10-second sickle kick speed test based on Johansyah Lubis guidelines. Data were analyzed using descriptive statistics, Shapiro-Wilk normality test, Levene homogeneity test, and paired sample t-test. The results showed an increase in the mean score from 19.15 in the pretest to 26.75 in the Posttest. The paired sample t-test indicated a significance value of 0.000 (p<0.05). Therefore, it can be concluded that resistance band and plyometric training significantly improve sickle kick speed among Pat Ban Bu Pencak Silat athletes.